Oligopeptide‐Induced Multifunctional Interface Layer with Protonated Hydrophobic Behavior and Strong Affinity for Highly Stable Zinc Anode - Liang, Xiao; Yang, Rui; Zheng, Yongping; Zhang, Fan; Zhang, Wenjun; Lee, Chun‐Sing; Tang, Yongbing (Advanced functional materials, 2025)
Zinc‐ion batteries (ZIBs) have attracted wide attention due to their low redox potential, high capacity, and intrinsic safety. However, key issues such as zinc dendrite growth, corrosion, and passivation on zinc anode detrimentally affect the electrochemical performance. Herein, as proof of a concept of oligopeptide, glutathione with functional groups including –NH2 and −SH is introduced as an electrolyte additive to construct a multifunctional electrode–electrolyte interface layer on the zinc anode. A protonated amino group (NH3+) is formed, which prevents the adsorption of water molecules on the Zn anode, building a hydrophobic interface layer and thus attenuating corrosion. Moreover, the strong interaction between the −SH and the zinc allows glutathione molecules to be tightly anchored to the electrode surface, constructing a robust interface layer. Consequently, a long cycling life of nearly 3000 h at 1 mA cm−2 for the Zn||Zn symmetric battery is achieved, and a stable cycling life of 1600 h is demonstrated at 3 mA cm−2. Furthermore, Zn||activated carbon (AC) hybrid capacitor with the glutathione‐containing electrolyte runs stably for nearly 28 000 cycles at 5 A g−1, among the best results of reported Zn hybrid capacitors. Glutathione with functional groups including protonated amino group (NH3+) and −SH is introduced as an electrolyte additive to construct a multifunctional electrode–electrolyte interface layer on the zinc anode, which is conducive to improve interfacial hydrophobic capacity and adhesive strength. Owing to these significant functions, the Zn‐AC hybrid capacitor exhibits ultralong cycle life for over 28 000 cycles at 5 A g−1.